Efficacy of Alexander Technique Versus Progressive Relaxation Technique in Improving the Functional Activity of Security Guards with Mechanical Low Back Pain- A Randomized Experimental Trial: Life Sciences-Nursing - M, Srinivasan; T, Murugaraj; K, Venkatesh; Hariharan N, Sabarish; E, Shanmugananth (International Journal of Life Science and Pharma Research, 2023)
Low Back Pain is quite common in them. Changes in posture or poor body mechanics may cause the above spine-related problems, causing other muscles to be misused and become painful. However, mechanical Low Back Pain usually does not cause weakness or numbness in the lower extremities because the problem is not due to compression of the spinal nerves. The study aims to compare the effectiveness of the Alexander and progressive relaxation techniques in inducing relaxation and improving the functional activity of individuals with mechanical low back pain. It is a simple experimental study. For the study, 40 subjects were divided randomly into groups, namely group A and group B, each consisting of 20 subjects. Group A was given the Alexander technique, and Group B was given the progressive relaxation technique. The Visual Analogue Scale and the Oswestry Disability Index were used.: The collected data were recorded and tabulated. The data were analyzed using the Statistical Package for Social Science (SPSS 20 version – USA ) to present the study's findings. Comparison of pre-and post-visual analog scale (VAS) using the Alexander technique shows pre-VAS 6.75 and post-VAS reduced to 2.55, given t-value 20.03, thus providing significant results with p< 0.001 s.s. Comparison of pre and post-VAS using progressive relaxation technique shows pre-VAS at 6.9 and post-VAS reduced to 3.6. Given a t-value of 14.91 gives a significant result with a p< 0.001. This study concluded that the Alexander technique is more effective in mechanical low back pain subjects. This study will help select interventions in mechanical low back pain subjects.